1997
DOI: 10.1007/bf01245959
|View full text |Cite
|
Sign up to set email alerts
|

Partial discharges in epoxy resin voids and the interpretational possibilities and limitations of Pedersen's model

Abstract: Contents Partial discharges take place, among others, inside voids enclosed in insulations. The partial discharge behaviour of epoxy resin samples is studied with the aid of a recently developed streamer partial discharge model (Iedersen's model) and its relation to the modem Pulse Height Analysis and Phase Resolved Measurement techniques is investigated. Furthermore, some relations based on Pedersen's model are deduced. The advantages and disadvantages of the aforementioned model are analysed. Scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 27 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Figure 3 shows sample traces corresponding to three different sources: a neutron event, an alpha-particle event, and a microdischarge from the proportional counter. Microdischarges are electronic artifacts originating from current leakage in the bias voltage breakdown applied to the counter [29,30,31]. To determine the pulse height of the waveform, one first removes the baseline offset by subtracting off the average of the first few hundred samples of the trace, well before the pulse onset.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Figure 3 shows sample traces corresponding to three different sources: a neutron event, an alpha-particle event, and a microdischarge from the proportional counter. Microdischarges are electronic artifacts originating from current leakage in the bias voltage breakdown applied to the counter [29,30,31]. To determine the pulse height of the waveform, one first removes the baseline offset by subtracting off the average of the first few hundred samples of the trace, well before the pulse onset.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…PDs usually occur as a result of the various defects, as described above. PDs in EMs cause typical patterns, the analysis of which can identify the origin of different PDs [18][19][20][21]. PDs can be categorized as [11]:…”
Section: Pds On Emsmentioning
confidence: 99%
“…Eight different water droplet setups were chosen (Figures [18][19][20][21], which one by one, were positioned on the sample surface of the epoxy resin. Eight different water conductivies were used, from 1.4 µS/cm to 10,000 µS/cm, in order to investigate how they affect the PD.…”
Section: Effect Of Humidity On Pdsmentioning
confidence: 99%
“…During ageing, an oxidized layer containing carbonyl radicals (=CO) appear at the cavity surface, which modifies its conductive characteristics, affecting indeed the PD inception and extinction magnitude, the electric field distribution and streamer landing pattern [32]. The non-uniform deposition of by-products cause that some areas are prone to experience intensive bombardment [38]. In epoxy specimens, the oxidation process is dependent on the curing process because it has been shown that when anhydride hardener is used it reacts with most of the oxygen leaving an atmosphere that is 80-98% nitrogen.…”
Section: Degradation Of Polymeric Materials Induced By Pds In Cavitiesmentioning
confidence: 99%
“…Taking into account theoretical and experimental studies [38,51], it is assumed that PDs in spherical cavities can incept treeing, these being the last stage of the aging process before breakdown. Once the electrical tree is incepted, i.e., the first tree channel has a length enough for develop self-sustained PDs independent from those at the cavity, electrical tree continues propagating via a physical degradation mechanism [31,41].…”
Section: Calculation Of the Degradation Induced By Pds And Life Estimation Approachmentioning
confidence: 99%